Pengaruh Human Capital dan Labor Intensity terhadap Kinerja Keuangan Perusahaan pada Sektor Energi dan Migas di Indonesia Periode 2021-2024 - Marshanda Putri Firdaus; Chicha Kurnianingrum; Indi Salwa Zahrina (MASMAN Master Manajemen, 2026)
This study is based on the increasingly rapid development of the knowledge-based economy, where human capital is now regarded as one of the important assets in creating a company’s competitive advantage, especially in the energy and oil and gas sectors in Indonesia. This study aims to determine the effect of human capital and labor intensity on corporate financial performance, which is proxied by Return on Assets (ROA) during the 2021–2024 period. The research method used is a quantitative approach with multiple linear regression analysis. The research data were obtained from sample companies selected using a purposive sampling technique. The results of the study show that human capital, proxied by Value Added Human Capital (VAHU), has a positive and significant effect on corporate financial performance. These findings indicate that good human resource management is capable of increasing the company’s profitability level. On the other hand, labor intensity is proven to have a negative and significant effect on financial performance. This indicates that a high level of company dependence on labor, without being balanced by operational efficiency, can reduce the company’s ability to generate profits. In addition, simultaneously both variables are able to explain 74.5% of the variation in Return on Assets (ROA), so it can be concluded that human capital and labor intensity have a considerable contribution to corporate financial performance. Based on these results, companies need to prioritize improving the quality and competence of the workforce rather than merely focusing on increasing the number of employees. This step is important to maintain the stability of corporate financial performance in the post-pandemic era. In addition, companies also need to effectively control labor costs so that a decline in net profit margins can be avoided.